Control of zoonotic diseases in Africa and Asia. The contribution of research to One Health - Roger, François (Perspective, 2012)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Zoonotic diseases cause 2.2 million deaths and 2.4 billion cases of human illness throughout the world. They are concentrated in lowand middle-income countries in Asia and Africa, but the whole world is at risk of a potential pandemic. To combat these diseases, the international organisations are promoting the One Health concept, which is aimed at jointly addressing human health, animal health and the environment. However, the implementation of this approach is encountering numerous technical, scientific and institutional difficulties. Research will facilitate this implementation. This is shown by the interdisciplinary research conducted in Africa and Asia, associating methods used in the fields of human health and animal health, as well as the different stakeholders within these sectors. The promising findings of this research are helping to define the content of the concept and prefigure the management of the One Health initiative."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Zoonotic diseases cause 2.2 million deaths and 2.4 billion cases of human illness throughout the world. They are concentrated in lowand middle-income countries in Asia and Africa, but the whole world is at risk of a potential pandemic. To combat these diseases, the international organisations are promoting the One Health concept, which is aimed at jointly addressing human health, animal health and the environment. However, the implementation of this approach is encountering numerous technical, scientific and institutional difficulties. Research will facilitate this implementation. This is shown by the interdisciplinary research conducted in Africa and Asia, associating methods used in the fields of human health and animal health, as well as the different stakeholders within these sectors. The promising findings of this research are helping to define the content of the concept and prefigure the management of the One Health initiative.